2012
DOI: 10.1890/10-2179.1
|View full text |Cite
|
Sign up to set email alerts
|

Demographic drivers of successional changes in phylogenetic structure across life‐history stages in plant communities

Abstract: Abstract. To gain insight into the ecological processes driving community reassembly in disturbed ecosystems, we assessed the phylogenetic dispersion of early-and late-successional tree species occurring in lowland forests of northeastern Costa Rica. Early-successional species were more closely related than expected by chance, whereas late-successional species tended to be less closely related than expected by chance. Then, we evaluated temporal changes in the phylogenetic structure of seedling and tree assemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
146
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(166 citation statements)
references
References 61 publications
14
146
6
Order By: Relevance
“…Consistent with this expectation, absolute difference in neighbor SLA and LDMC was associated with significantly higher survival, suggesting niche differences among neighbors, and these same traits also showed greater neighborhood trait diversity in older stands. We previously observed increasing phylogenetic diversity with stand age in our plots (46), which assuming that traits are conserved, is likely influenced by trait-mediated niche differences. However, the demographic effects of traitmediated niche differences were countered by strong trait correlations with average demography, suggesting that assembly simultaneously changed community trait means and variance.…”
Section: Discussionmentioning
confidence: 50%
“…Consistent with this expectation, absolute difference in neighbor SLA and LDMC was associated with significantly higher survival, suggesting niche differences among neighbors, and these same traits also showed greater neighborhood trait diversity in older stands. We previously observed increasing phylogenetic diversity with stand age in our plots (46), which assuming that traits are conserved, is likely influenced by trait-mediated niche differences. However, the demographic effects of traitmediated niche differences were countered by strong trait correlations with average demography, suggesting that assembly simultaneously changed community trait means and variance.…”
Section: Discussionmentioning
confidence: 50%
“…First, logging would assimilate environmental conditions of primary forest to those of early successional forest and this environmental homogenization would result in phylogenetic clustering by increasing specific clades with similar environmental requirements. On the other hand, recruitment would recover a floristic composition typical of original primary forest resulting in phylogenetic evenness [35]. Second, but not always alternatively, phylogenetic clustering may have resulted as a by-product of species loss.…”
Section: Discussionmentioning
confidence: 99%
“…Community phylogenetic indices analyse phylogenetic patterns within and between communities and can help to understand underlying ecological mechanisms [26,27]. Previous studies showed that within-community phylogenetic clustering was observed in secondary, early stage and poor nutrient forests because related species are more likely to be ecologically similar and live in the same habitat [33][34][35][36][37]. On the other hand, withincommunity phylogenetic evenness was observed in primary and late stage forests probably because of the competitive exclusion among related species [33][34][35][36], although other ecological processes can be assumed [38].…”
Section: Introductionmentioning
confidence: 99%
“…2002, Westoby & Wright 2006; Poorter et al., 2008; Chave et al. 2009; Norden, Letcher, Boukili, Swenson, & Chazdon, 2012; Buzzard, Hulshof, Birt, Violle, & Enquist, 2016). However, comparative analyses of demographic performance of species with contrasting sexual systems in diverse forests at different successional stages are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Monoecy in the plant lineage correlates with the evolution of dioecy (occurring in the same tree families and/or in closely related families; Renner & Ricklefs, 1995). However, phylogenetic relationships between species may influence comparisons among species in terms of responses to both biotic and abiotic conditions in natural habitats (Norden et al., 2012; Russo et al., 2010). Quantifying the relationships between demographic dynamics and breeding systems considering the effects of phylogeny at different successional stages could provide new insights into the complex interacting processes that shape community dynamics across large temporal scales (Chang & HilleRisLambers, 2016).…”
Section: Introductionmentioning
confidence: 99%